Navigation et milieu fluvial au XIe s. L'épave d'Orlac (Charente-Maritime) - Chapelot, Jean; Rieth, Éric (Documents d'archéologie française, 1995)
The Orlac boat (Charente-Maritime), dated to the first-half of the XIth century and excavated in 1987 and 1988, comprises the major part of this publication. 15,50 metres in length and 2,10 in width, this vessel, with its own particular caracteristics, is representative of assembled monoxyle boat architecture. The study of this wreck was at the same time combined with a study of river and riverbank improvements at Orlac, and with other medieval wrecks (essentially dug outs) excavated elsewhere in the Charente. This archaeological approach to medieval water transport of the Charente has been continued by an analysis of written sources, the progression of river improvements (Middle-Ages to XIXth century), of navigation and their consequences on the regional economy.